Dense nanocrystalline W alloys: Enhancement of hardness and thermal stability by Al addition. (April 2023) - Torre, Francesco; Huminiuc, Teodor; Barra, Paolo; Pilloni, Luciano; Polcar, Tomas; Rinaldi, Antonio; Delogu, Francesco; Orrù, Roberto; Cao, Giacomo; Locci, Antonio Mario
Abstract: Nanocrystalline W100- x Al x ( x up to 20 at.%) powders obtained by mechanical alloying have been consolidated by spark plasma sintering (SPS). Alloying W with Al significantly improves the sinterability, allowing the fabrication of dense samples. The consolidation process keeps the nanocrystalline microstructure substantially unaffected, which contributes to the hardness of the final W-Al alloys. The room-temperature nano- and micro-hardness of dense W80 Al20 alloy sintered at 1100 °C are as high as 18 and 14 GPa, respectively. These values are significantly higher than those previously reported for pure coarse- or submicron-grained W and may be ultimately ascribed to the grain boundary segregation of Al. Highlights: Single-phase nanocrystalline W100- x Al x ( x = 0–20 at.%) powders were prepared. Dense samples (up to 96% of relative density) of W-Al alloys were obtained. It was shown that Al addition could significantly improve the sinterability of powders. The consolidated W-Al samples exhibit nanohardness in the range of 18–19.5 GPa and Vickers hardness up to about 16 GPa.